Atomistic–continuum model for probing the biomechanical properties of human erythrocyte membrane under extreme conditions - Ademiloye, A.S.; Zhang, L.W.; Liew, K.M. (Computer methods in applied mechanics and engineering, 2017)
A precise first attempt is performed to quantify the biomechanical properties of human erythrocyte membrane subjects to extreme temperature and loading conditions. An improved three-dimensional (3D) atomistic–continuum model based on the Cauchy–Born rule is proposed to investigate the elastic properties and biomechanical responses of the erythrocyte membrane. A membrane rigidity model is developed to estimate the membrane elastic properties over an extreme temperature range. Our computational results reveal that the membrane is able to sustain large strains up to a certain limit; beyond which, mechanically induced hemolysis may occur as exponential stress increment, fluctuations and multiple peaks were observed in the stress–strain curves. Additionally, we found that the overall deformability of the erythrocyte membrane significantly decreases as temperature increases. It is concluded that the observed increase in membrane rigidity may be attributed to the denaturation, structural remodeling and cross-linking of membrane cytoskeletal proteins.